Lecture Notes in Computer Science
DOI: 10.1007/978-3-540-70918-3_52
|View full text |Cite
|
Sign up to set email alerts
|

Quantum Network Coding

Abstract: Since quantum information is continuous, its handling is sometimes surprisingly harder than the classical counterpart. A typical example is cloning; making a copy of digital information is straightforward but it is not possible exactly for quantum information. The question in this paper is whether or not quantum network coding is possible. Its classical counterpart is another good example to show that digital information flow can be done much more efficiently than conventional (say, liquid) flow. Our answer … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
127
1

Publication Types

Select...
3
3
3

Relationship

2
7

Authors

Journals

citations
Cited by 136 publications
(128 citation statements)
references
References 27 publications
0
127
1
Order By: Relevance
“…As shown in the figure, we can transmit two bits, x and y, on the two paths simultaneously. The paper [9] extends this network coding for quantum channels and quantum information. Their results include; (i) One can send any quantum state |ψ 1 from s 1 to t 1 and |ψ 2 from s 2 to t 2 simultaneously with a fidelity strictly greater than 1/2.…”
Section: Applications To Network Codingmentioning
confidence: 88%
“…As shown in the figure, we can transmit two bits, x and y, on the two paths simultaneously. The paper [9] extends this network coding for quantum channels and quantum information. Their results include; (i) One can send any quantum state |ψ 1 from s 1 to t 1 and |ψ 2 from s 2 to t 2 simultaneously with a fidelity strictly greater than 1/2.…”
Section: Applications To Network Codingmentioning
confidence: 88%
“…Quantum multicast was studied by Shi and Soljanin [77], who showed that lossless compression of special multicast quantum states is possible and significantly reduces the edge capacity requirements of the multicast. Two unicasts on the butterfly network of quantum channels were first considered by Hayashi et al [32], who showed that two qubits can be sent simultaneously with keeping their fidelity strictly greater than 1/2 if the nodes of the network can use one of the available algorithms for approximate cloning [7]. This approach was later extended to probabilistic cloning and general graphs by Iwama et al [38].…”
Section: Notesmentioning
confidence: 99%
“…It is expected that network coding also allows the same resolution in a quantum network. In recent years, a number of researchers have studied quantum network coding [21][22][23][24][25][26][27] . However, all of these studies presuppose the use of pure states and perfect local gates.…”
Section: Introductionmentioning
confidence: 99%